An Analysis Students’ Vowel in Pronunciation - Damitra Paolo Purba; Meilia Novianty Bangun; Enda Putri Pramana; Rudi Martono Jaya Sinaga; Sri Ninta Tarigan (Linguistic, English Education and Art (LEEA) Journal, 2019)
This research aimed to find out the pronunciation correctly and incorrectly made by the eighth grade at SMP Swasta Puteri Sion in terms of vowels sound. The method of the research is a case study in the form of qualitative research method. The total samples of this research are 22 students. There are 36 vowels sound which include in the dialogue that will be analyzed by the researcher. The research result showed that 19 words incorrectly pronounced by the students with percentage 53% and 17 words are correctly pronounced by students with percentage 47%. The students could not pronounce the phonetic symbols correctly, they will pronounce well only as long as the words are familiar for them. In this case, the students need to more learn and read about phonetic symbol at the school and outside the school. In relation to this, encourage the students need to more learn and read about phonetic symbol at the school and outside the school by listening English music, reading a English novel and watching English movie to improve their skill in pronunciation. Keyword: pronunciation, vowels